The role of psychosocial factors in Black women's self‐efficacy in receiving genetic counseling and testing. Issue 6 (4th June 2021) - Ding, Huanghe; Sutton, Arnethea L.; Hurtado‐de‐Mendoza, Alejandra; Sheppard, Vanessa B.
Abstract: Higher self‐efficacy in receiving genetic counseling and testing (GCT) has been associated with greater participation in GCT for women at risk of hereditary breast and ovarian cancer (HBOC), but little is known about correlates of self‐efficacy in Black women eligible for GCT. The goal of this secondary analysis was to identify sociodemographic and psychosocial factors regarding GCT. Multivariable regression analysis was conducted to assess the relationship between self‐efficacy and correlates of interest. Of the 100 Black women surveyed, most women had a college degree (64%), were employed (84%), and had health insurance (93%). In the multivariable model, greater self‐efficacy was associated with more positive attitudes toward GCT ( Β  = 0.126; CI = 0.01 to 0.25; p  = 0.039), greater confidence in the Genetic Information Nondiscrimination Act (GINA) ( Β  = 0.250; CI = 0.04 to 0.46; p  = 0.019), and lower ratings of perceived difficulty obtaining GCT ( Β  = −0.219; CI = −0.46 to −0.10; p  = 0.003). Community‐level interventions to promote self‐efficacy are needed that address perceived barriers to GCT, with the goals of increasing GINA Law awareness in the general public, increasing accessibility to genetic counseling (e.g., telemedicine), and promoting more positive attitudes about GCT.